Hubungan Antara Pengelolaan Zakat Produktif Dengan Peningkatan Kesejahteraan Mustahiq Pada Laznas Yatim Mandiri Cabang Surabaya - Fajri, Rochmawati; Ajib Ridlwan, Ahmad (Jurnal Ekonomika dan Bisnis Islam, 2019)
This is a study aims to determine the mechanical picture of managing productive zakat in the Surabaya Branch of the Independent Amil Zakat Institution and the impact of improving the welfare of mustahiq under the guidance of the Orphaned National Amil Zakat Institution The management of productive zakat must be directed as an instrument in developing the welfare standard of mustahiq. This research method uses a quantitative approach. The data analyzing collection efforts were used by rank-spearsman correlation data. The results of the research that have been carried out with the variable management of productive zakat and improvement of mustahiq welfare with indicators of supervision, training, religion, soul, reason, descent and wealth, using simple random sampling technique with the distribution of questionnaires can be concluded that the management of productive zakat has a strong and significant relationship to increase in mustahiq welfare at the Surabaya branch of the Orphaned National Amil Zakat Institution